2018
DOI: 10.11613/bm.2019.010501
|View full text |Cite
|
Sign up to set email alerts
|

A review of urinary angiotensin converting enzyme 2 in diabetes and diabetic nephropathy

Abstract: Urinary angiotensin converting enzyme 2 (ACE2) is significantly increased in diabetes and diabetic nephropathy. While studies on its clinical significance are still underway, its urinary expression, association with metabolic and renal parameters has been in the recent past considerably studied. The recent studies have demystified urine ACE2 in many ways and suggested the roles it could play in the management of diabetic nephropathy. In all studies the expression of urinary ACE2 was determined by enzyme activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 46 publications
0
16
0
2
Order By: Relevance
“…Increased ACE2 levels in urine, cerebrospinal fluid, and plasma may in fact correspond to a decreased ACE2 activity at the tissue level ( Anguiano, Riera, Pascual, & Soler, 2017 ; A. Gilbert et al, 2019 ; Palau, Pascual, Soler, & Riera, 2019 ; Úri et al, 2014 ). Nevertheless, both in vitro and in vivo experiments provide crucial information on the action mechanisms of drugs and guidance for further clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Increased ACE2 levels in urine, cerebrospinal fluid, and plasma may in fact correspond to a decreased ACE2 activity at the tissue level ( Anguiano, Riera, Pascual, & Soler, 2017 ; A. Gilbert et al, 2019 ; Palau, Pascual, Soler, & Riera, 2019 ; Úri et al, 2014 ). Nevertheless, both in vitro and in vivo experiments provide crucial information on the action mechanisms of drugs and guidance for further clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the ACE2/Ang-(1-7)/A2R/MasR axis is considered to be a multi-organ protector opposing the ACE/Ang2/AT1R axis. The function of sACE2 remains unclear, but high levels of sACE2 were found in patients with SARS [65], type 1 or type 2 diabetes [44], hypertension [167], heart failure [1], and chronic kidney diseases [1], suggesting that increased sACE2 may act in a protective manner to counteract the adverse effects of Ang2. SARS-CoV-infected wild-type mice had significantly reduced ACE2 expressions in the lung [74] and heart [110].…”
Section: The Physiology Of the Renin-angiotensin System And Ace2mentioning
confidence: 99%
“…A large cohort study showed that circulating ACE2 was only detectable in the serum of 40 among 534 test subjects, and its concentration was approximately 100-fold lower than that of circulating ACE [30]. More evidence showed that circulating ACE2 is increased in patients with type 1 or type 2 diabetes, hypertension, heart failure, and chronic kidney diseases [31][32][33]. The reason for high levels of ACE2 in these patients is that increased ACE2 is a defensive response to counteract the adverse effect of Ang II.…”
Section: Functions Of Ace2mentioning
confidence: 99%